Pengaruh Literasi Keuangan, Gaya Hidup, dan Locus of Control Terhadap Perilaku Keuangan Generasi Z pada Cashless Society - Nur Fatimah, Septiana; Fathihani, Fathihani (Jurnal Ilmu Manajemen Terapan, 2023)
This study aims to measure the effect of financial literacy, lifestyle and locus of control as independent variables, on financial behavior in the cashless society as the dependent variable. The sample used is generation Z in DKI Jakarta who uses non-cash transactions. The sampling method uses a purposive sampling method where the researcher has determined the sampling by determining the specific characteristics that are in accordance with the research objectives. This research analysis uses multiple linear regression analysis with a significance level of 5 percent, which is processed using the Statistical Package for Social Science (SPSS) version 25 program. The results of this study indicate that 1) Financial Literacy has a positive effect on Financial Behavior. 2) Lifestyle has a positive effect on Financial Behavior. 3) Locus of Control has no effect on Financial Behavior, 4) Financial Literacy, Lifestyle, and Locus of Control have a positive effect on Financial Behavior.